Intracorneal Stromal Ring Can Affect the Biomechanics of Ectatic Cornea - Shahram Bamdad; Mohammad Reza Sedaghat; Masoud Yasemi; Mehrnoosh Maalhagh (Journal of Ophthalmology)
Purpose. The biomechanical properties of ecstatic cornea undergo changes. This study evaluates the biomechanical changes of ecstatic cornea after implantation of two types of intracorneal stromal ring (ICR). Methods. For doing this prospective cross-sectional study, 32 patients with keratoconus (KCN) were randomly divided into two 16-member groups (group I: MyoRing, group II: KeraRing). The main inclusion criteria were transparent cornea with no scar in the central part, corneal thickness >450 µ in the incision region, keratometry within 48–52 diopters, and progressive course of corneal thinning. Biomechanics of the cornea was evaluated by “ORA” and “Corvis” devices. All of the data were recorded and analyzed before implantation of the rings and 6 months thereafter. Results. The mean ages of patients of groups I and II were 26 ± 6.55 and 33.86 ± 8.5, respectively. The postoperative change of sphere refraction was significant in both groups. However, reduction in the astigmatism was significant only in group I. In addition, the change of flat meridian keratometry (Kf) was significant before and after ring implantation in group I, unlike group II. The changes in CH and CRF parameters (ORA) were not significant in either group before and after the operation. Besides, only HRC parameter (Corvis) decreased significantly in both groups before and after the operation. Conclusion. Both MyoRing and KeraRings have positive effects on the biomechanics of cornea at least during the first year after implantation. Comparison of these two types of ICR did not show significant differences in Corvis and ORA parameters.